Perspectivas y alternativas de América Latina ante los problemas mundiales - Urquidi, Víctor L.; Sánchez, Vicente; Terrazas, Eduardo (Estudios Internacionales, 1981)
This paper presents some ideas and comments on the perspectives of Latin America and some of the alternatives for confronting and resolving their particular situation, relating to the world problem. For this, it is convenient to describe some premises and characteristics of the levels of disaggregation with which we operate when approaching the issue of global interrelations. The basic premise is that the articulation of man with nature has become increasingly inadequate, expressed in a series of "crises" that constitute different facets of the global crisis. Latin America is in need of re-evaluating its "project" in its own terms and of generating congruence between its cultural and political goals, on the one hand, and its potential in resources and its technical and organizational capacity, on the other.